2014
DOI: 10.1016/j.neuron.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive Axonal Transport Deficits in Multiple Sclerosis Models

Abstract: Impaired axonal transport can contribute to axon degeneration and has been described in many neurodegenerative diseases. Multiple sclerosis (MS) is a common neuroinflammatory disease, which is characterized by progressive axon degeneration-whether, when, and how axonal transport is affected in this condition is unknown. Here we used in vivo two-photon imaging to directly assay transport of organelles and the stability of microtubule tracks in individual spinal axons in mouse models of MS. We found widespread t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
184
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 151 publications
(206 citation statements)
references
References 36 publications
(52 reference statements)
14
184
0
3
Order By: Relevance
“…Disturbances of axonal transport and metabolism, often visualized by immunohistochemistry for axonally transported proteins, such as amyloid precursor protein (APP) or SMI32, a marker for dephosphorylated neurofilaments of damaged axons, are most abundant in early stages of lesion formation and, according to experimental data, only a proportion of these damaged axons will undergo axonal transection (Sorbara et al, 2014; Nikic et al, 2011; Trapp et al, 1998). A number of inflammatory mediators have been accused to impair axonal function, mainly derived from phagocytes actively stripping off the myelin sheaths in early lesions (Clark et al, 2016; Cunningham, 2013; Lassmann, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances of axonal transport and metabolism, often visualized by immunohistochemistry for axonally transported proteins, such as amyloid precursor protein (APP) or SMI32, a marker for dephosphorylated neurofilaments of damaged axons, are most abundant in early stages of lesion formation and, according to experimental data, only a proportion of these damaged axons will undergo axonal transection (Sorbara et al, 2014; Nikic et al, 2011; Trapp et al, 1998). A number of inflammatory mediators have been accused to impair axonal function, mainly derived from phagocytes actively stripping off the myelin sheaths in early lesions (Clark et al, 2016; Cunningham, 2013; Lassmann, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A number of inflammatory mediators have been accused to impair axonal function, mainly derived from phagocytes actively stripping off the myelin sheaths in early lesions (Clark et al, 2016; Cunningham, 2013; Lassmann, 2014). Experimentally, NO and ROS, highly reactive lipid soluble mediators, are responsible for an important share of the acute axonal damage observed (Nikic et al, 2011; Sorbara et al, 2014). In addition to therapeutically addressing the plethora of inflammatory mediators present, remyelination of axons is considered as one of the most important endogenous axon‐protective mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The chronic inflammation results in microglia and macrophage activation producing reactive oxygen and nitrogen species (ROS/NOS) which can lead to mitochondrial damage [26,27] (reviewed in [28]), metabolic stress, protein misfolding and deceased axonal transport [29,30]. Accumulating evidence suggests genuine hypoxia as another mechanism contributing to the tissue injury in acute as well as chronic MS lesions [31][32][33].…”
Section: The Pathogenic Cascade Leading To Neurodegenerationmentioning
confidence: 99%
“…Considering that both cerebellar lesions and genetic mutations in diseases such as the inherited spastic ataxias cause changes in muscle tone [220][221][222] , our data suggests that neurodegeneration of the VSCT might also contribute to spasticity, which was readily apparent in the anti-hnRNP A1 antibody injected mice. These data add to the growing body of evidence that EAE is a suitable animal model to study neurodegeneration mechanisms that may be applicable to MS. 148,194,195,[223][224][225] Neurodegeneration is now believed to be the primary cause of permanent, longterm disability in MS patients. 187,188,192,193 Data indicate neuronal and axonal damage in an ongoing process in MS. 7,9,13,186,187 In some patients, it begins during the relapsing, remitting phase of MS (RRMS) and continues into secondary progressive MS (SPMS).…”
Section: Amentioning
confidence: 99%
“…7,191,219 In animal models, axonal degeneration results from a specific sequence of events, which include impaired axonal transport, mitochondrial dysfunction and increase in intraaxoplasmic calcium. 218,225 Importantly, each of these abnormalities has been found in brains of MS patients as well as in EAE, and have been implicated in the pathogenesis of neurodegeneration. Several studies have shown that mitochondrial injury and associated oxidative damage, production of reactive oxygen species and induction of apoptosis contribute to axonal injury.…”
Section: Amentioning
confidence: 99%